Ilmiy tadqiqotchilik faoliyatini amalga oshirish mexanizmi (SCIENCE and SOCIETY, 2023)
The article analyzes the content of scientific research activity and modern requirements for its compo- nent, as well as ways to achieve their effectiveness in the process of scientific activity.